Bioprospecção e Avaliação de Rizobactérias com Potencial de Promoção de Crescimento Vegetal para a Cultura do Feijoeiro - Souza, Luana de (2025)
Common bean (Phaseolus vulgaris L.) is a crop of significant social and economic importance in Brazil. However, its production faces challenges such as low soil fertility and excessive use of nitrogen fertilizers, which generate negative environmental impacts. As a sustainable alternative, the use of beneficial microorganisms, such as rhizobia and plant growth-promoting bacteria (PGPB), stands out. These microorganisms fix atmospheric nitrogen, solubilize nutrients, and produce phytohormones, aiding plant development and stress resistance. This study focused on the prospection and characterization of native rhizobacteria from soils in Paraná (Guartelá State Park, Iguaçu National Park and Cafelândia), aiming at their application in bean cultivation for more sustainable agricultural practices. A total of 90 bacteria were isolated, with 65.56% demonstrating biological nitrogen fixation (BNF) capacity and 6.67% solubilizing phosphorus. Notable isolates include PNI99 (Bacillus sp.) and CAF83 (Bacillus safensis), which exhibited efficiency in potassium solubilization, BNF, and siderophore production. B. safensis also significantly increased the dry root weight of bean seedlings during germination. The results indicate that these rhizobacteria, particularly B. safensis, have high potential as bioinoculants, capable of reducing reliance on chemical fertilizers and promoting sustainable bean growth, thereby contributing to soil health and the reduction of agriculture's environmental impacts.